2012
DOI: 10.1161/strokeaha.111.637884
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Intra-Arterial Neural Stem Cell Transplantation After Hypoxia–Ischemia Influences Cell Engraftment, Survival, and Differentiation

Abstract: Background and Purpose-Intra-arterial neural stem cell (NSC) transplantation shows promise as a minimally invasive therapeutic option for stroke. We assessed the effect of timing of transplantation on cell engraftment, survival, and differentiation. Methods-Mouse NSCs transduced with a green fluorescent protein and renilla luciferase reporter gene were transplanted into animals 6 and 24 hours and 3, 7, and 14 days after hypoxia-ischemia (HI). Bioluminescent imaging was used to assess cell survival at 6 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 30 publications
5
62
0
1
Order By: Relevance
“…5). Previous data from our lab and others have found that SDF-1 is highly upregulated 3 days after stroke (15,35), and the interaction of SDF-1 with CXCR4 plays an important role in facilitating migration of cells in the ischemic brain (36). Our data corroborates recent evidence that overexpression of CXCR4 in intravascularly transplanted mesenchymal stem cells improves engraftment (37), and we postulate that the significant change in migratory ability of NSCs seen after BDNF pretreatment could contribute to greater cell engraftment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5). Previous data from our lab and others have found that SDF-1 is highly upregulated 3 days after stroke (15,35), and the interaction of SDF-1 with CXCR4 plays an important role in facilitating migration of cells in the ischemic brain (36). Our data corroborates recent evidence that overexpression of CXCR4 in intravascularly transplanted mesenchymal stem cells improves engraftment (37), and we postulate that the significant change in migratory ability of NSCs seen after BDNF pretreatment could contribute to greater cell engraftment.…”
Section: Discussionsupporting
confidence: 90%
“…Representative sections were 400 µm apart (five representative sections, three from the cortex, two from the hippocampus; each representative section 400 µm apart, for a total of 2 mm of brain analyzed) and chosen by an investigator blinded to treatment groups. ROIs in peri-infarct regions were chosen based on previous data from our lab illustrating the commonly affected regions of the brain after HI stroke (30,35). A different blinded investigator then performed the unbiased counting of SC-121 + cells.…”
Section: Cell Quantificationmentioning
confidence: 99%
“…Immunohistochemical and immunofluorescence staining verified that iPSCs and NSCs migrated to the area close to the ischemic area, where they expressed the mature neuronal marker NeuN, mature astrocyte marker GFAP, and endothelial cell marker vWF. These findings corroborate other previous studies (on NSCs or iPSCs used individually), which demonstrated that stem cells survived, migrated, and differentiated into mature neurons (26) or angiogenic cells (19) and improved functional recovery via promoting vascular endothelial growth factor expression and enhancing endogenous plasticity in the injured brain (27). Transplantation of iPSCs could improve the motor function, reduce infarct size, attenuate inflammation cytokines, and mediate neuroprotection after ischemic stroke (10,28).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, the time of cellular intervention post ischemic insult is integral to the accomplishment of the desired prognosis. Although methodical and in-depth studies to ascertain optimal intermission between stroke to cell transplantation are still wanting in the literature, various research groups have performed cell transplantation from hours to weeks after ischemic stroke (36,37). Our study was aimed to ascertain the optimal time for cell therapy after stroke in terms of attenuation of cell apoptosis in the host tissue and overall improved neurological performance.…”
Section: Discussionmentioning
confidence: 99%